Conservation Voltage Reduction in Distribution Networks: A Comprehensive Review - Ibrahim Alzubi; Saher Albatran; Issam A. Smadi; Salman Harasis (IEEE Access)
Conservation voltage reduction (CVR) is an efficient technique that lowers voltage levels to reduce aggregated energy consumption and achieve peak demand shaving in distribution networks. Utilities have considered CVR as a cost-effective technique to improve energy efficiency and reduce customers’ bills. This paper bridges the gap between theory and practice by providing a comprehensive and systematic review of CVR research progress from various aspects, including the effects of CVR on the operation and efficiency of both individual loads, such as residential appliances, and composite commercial and industrial loads. Engineers need to know the detailed CVR assessment methodologies in the literature, including (i) comparison-based, (ii) regression-based, (iii) load modeling-based, and (iv) simulation-based methods. Existing techniques of CVR implementation, including voltage/VAR control (VVC) and voltage/VAR optimization (VVO), are detailed to clarify practical applications working in the field, allowing researchers to develop and improve. Afterward, a complete review of the CVR utilization in active distribution networks with the presence of distributed generation (DG) and integrating CVR in microgrid applications is carried out. In addition, a survey about the economic benefits of CVR for both utilities and customers is analyzed. This paper gives engineers and researchers a handy tool to evaluate the state-of-the-art critically, clarify the latest and advanced technologies, and highlight challenges, limitations, and further developments in CVR applications.